Effect of X-ray Tube Voltage Variation on Signal to Noise Ratio (SNR) by Application of Anode Heel Effect using Stepwedge - Luh Gede, Puja Satwika; Ratini, Ni Nyoman; Iffah, Maghfirotul (BULETIN FISIKA, 2020)
It has been conducted research to determine the effect of X-ray tube voltage variation (kV) on Signal to Noise Ratio (SNR) values by applying the Anode Heel Effect using stepwedge with the addition of 1.5 mm thickness each step. The stepwedge used was 1.5-31.5 mm. The X-ray tube voltage variations used were 40, 50, 60, 70, 80, and 90 kV. Analysis of the effect of X-ray tube voltage variation on SNR values is determined using IMB SPSS Statistics 26 with a simple regression test. The test results showed that variations in X-ray tube voltage affect SNR values, where the greater the variation in X-ray tube voltage then the SNR value would get smaller. The optimal SNR value of 72.685 was obtained at a tube tension of 40 kV and a stepwedge thickness of 27.0 mm.